Polypharmacy and multimorbidity in Post-polio syndrome: Evidence of risks? (Research, Society and Development, 2022)
The Post-poliomyelitis Syndrome (PPS) has as a therapeutic measure the use of medications for its symptoms; however, the use of different drugs for other morbidities is also perceived. The article aimed to investigate the pharmacotherapeutic profile of patients with PPS treated at a Brazilian tertiary outpatient clinic, as well as the practice of polypharmacy and its association with demographic and socioeconomic indicators, chronic diseases and symptoms of PPS. A descriptive, cross-sectional study was carried out with 150 patients diagnosed with PPS, and through a form, demographic, socioeconomic, clinical and pharmacotherapeutic data were obtained. The mean age of patients was 53 years; 74% female; 42.6% with 13 years of study or more; 93.3% with their own economic income and 96% of independent patients with other morbidities with an average of 4 morbidities/patient, with Arterial Hypertension being the most prevalent (45%). Patients used up to 14 medications, with an average of 5 medications/patient – presence of Polypharmacy (52%); 72.6% used medications that act on the nervous system – higher prevalence of antidepressants. It was found by the Chi-square test, statistically significant associations p